ʽYou're not getting rid of usʼ. Performing acts of citizenship in times of emigration. Issue 2 (17th February 2019) - López-Sala, Ana
ABSTRACT: This article uses academic literature on acts of citizenship and performative citizenship to investigate the contestation, protest, and resistance actions carried out by the Marea Granate collective in defence of the citizenship rights of Spanish citizens living abroad. Marea Granate (Maroon Wave) is a transnational network of young Spanish emigrants that emerged in 2013 as a result of the recent widespread emigration provoked by the economic crisis and austerity politics in Spain. Based on their shared identity as economic exiles and demanding the right to participate in Spanish political life to change the conditions that led them to emigrate, the members of this organization have been carrying out innovative, creative citizenship acts that are breaking conventions and causing ruptures in the Spanish citizenship regime. These 'transformative acts of recovering ', the term used to refer to Marea Granate's demands and struggles for citizenship, have proven to be capable of being a driving force for change and also reveal the fluid and contested nature of citizenship in the contexts of austerity and emigration.